2013
DOI: 10.3136/fstr.19.1085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carvacrol and Volatile Fraction of Winter Savory (Satureja montana L.) on Body Temperature in Humans Who Experience Cold Sensitivity

Abstract: Ingestion of winter savory extract has been reported to inhibit the decrease in peripheral body temperature in people who experience cold sensitivity. However, the active ingredients underlying this effect are not known. We sought to elucidate the effects of the volatile components of winter savory on body temperature. Carvacrol (the main volatile component and a transient receptor potential channel ankyrin 1 (TRPA1) agonist in winter savory) increased core body temperature, but did not inhibit the decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…2 with that from a previous study (Masuda et al, 2013), CBT showed a different tendency as follows: in the previous study, CBT after ingestion of WSV was significantly higher than that after ingestion of the placebo; whereas, in Exp. 2, CBT after ingestion of WSV showed a lower tendency compared to that after ingestion of the placebo.…”
Section: ) or Placebo In Exp 3 Comparing The Time-course Of Changes Inmentioning
confidence: 40%
See 4 more Smart Citations
“…2 with that from a previous study (Masuda et al, 2013), CBT showed a different tendency as follows: in the previous study, CBT after ingestion of WSV was significantly higher than that after ingestion of the placebo; whereas, in Exp. 2, CBT after ingestion of WSV showed a lower tendency compared to that after ingestion of the placebo.…”
Section: ) or Placebo In Exp 3 Comparing The Time-course Of Changes Inmentioning
confidence: 40%
“…2) with those after ingestion of WSV (the amounts of thymol and carvacrol in WSV are the same as those in the mixture used in Exp. 3) reported by Masuda et al (2013). As a result, the ingestion of the mixture (in Exp.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations